Occupational injuries among fisherman in Tamil Nadu - An explanatory mixed methods study - B. Raghuramumar; R. Sindhuri; R. Muruganandham; Pravin Surendran; Reenaa Mohan (Journal of Current Research in Scientific Medicine)
Background: Fishing is one of the oldest and most dangerous occupations in the world which plays a major role in socio-economic development of the country and also offers livelihood and food security to fisherman. The objective of the study was to find out the prevalence of occupational injuries and its perceived reasons among fisherman at Cuddalore district of Tamil Nadu. Materials and Methods: It was a community-based explanatory mixed methods study (questionnaire survey with a representative sample of 250 fishermen followed by in-depth interviews among ten purposively selected fishermen aged 20–70 years). Quantitative data were entered and analyzed using Epi_info (version 3.5.4) software and the qualitative data were subjected to manual content analysis. Results: Of the total participants, 30% of them sustained injury in the past 1 month and hand was the most commonly injured part. The reasons perceived by the fishermen for occupational hazards falls under four categories namely personal (Poor health, addiction to alcohol, lack of experience), job-related (long working hours, handling heavy weight, unstable work surface), environmental (climate and rough sea) and economic (increased competition and poor earning). Conclusion: Nearly one out of three fishermen reported to have sustained injuries during work. Poor health condition, lack of experience, slippery floors and handling of heavy and sharp equipment were perceived as reasons for injuries by fishermen. The use of appropriate personal protective equipment, conducting on job training for young fishermen and organizing periodic medical examinations for all fishermen will aid in preventing occupational injuries.